Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu dan Kinerja Guru di SDN Bojong Rawalumbu VI - Rizky Budi Nugraha (Journal on Education, 2023)
This research aims to analyze and demonstrate the principal's leadership style in planning each school program; carry out the implementation of school programs; supervise school programs; evaluate the performance of teachers and school programs; and overcoming obstacles and supports in the implementation and design of school programs. This research was conducted using a qualitative approach or method. Through case studies that directly see, analyze and research at SDN Bojong Rawalumbu VI. This study also uses data collected through observation, interviews and documentation studies, data analysis using qualitative analysis with activity steps; reduction; presentation of field data; drawing conclusions and verifying. The results of this study indicate that: school principal planning includes, namely: compiling various annual school programs; carry out the implementation of learning programs and the vision and mission that have been designed, carried out routinely and efficiently; carry out clinical supervision or in-depth supervision of teacher performance; evaluating teacher programs and performance so that they are in line with the school program plans that have been made; overcoming obstacles that occur in the implementation of school programs and always involving all stakeholders or members of the school community in supporting the school's vision and mission to improve the quality of education and teacher performance at SDN Bojong Rawalumbu VI.